Consumers' identification of greenwashing in corporate marketing - Sievänen, Lotta (2025)
This thesis examines how consumers can identify the greenwashing of corporate marketing communications and what factors influence this ability. The research is based on a qualitative study using semi-structured thematic interviews with ten participants, the target audience for environmental claims through different media. The results show that while consumers are generally critical of environmental claims, their ability to identify greenwashing varies considerably depending on individual factors such as education, critical thinking skills, media literacy, and personal experience. Interviewees who watch corporate marketing on social media were found to pay more attention to visual and emotional cues, while those who follow traditional media focused more on clarity of terminology and the existence of concrete evidence. Education and media literacy were found to be key tools for identifying misleading environmental cues, but trust in familiar certificates and traditional media sources also played a key role. The study underlines that although many consumers are sceptical about green marketing, this does not always lead to a change in behaviour. Moreover, the responsibility for identifying greenwashing is often unfairly placed on consumers, despite the complexity of environmental communication. The results highlight the need for clearer regulation, more transparency in corporate sustainability communication, and the inclusion of environmental and media literacy in education to help consumers better evaluate green claims.